In situ carbon uptake of marine macrophytes is highly variable among species, taxa, and morphology - Jacobs, Julian M.; Himes, Lucian; La Valle, Florybeth F. (Frontiers in Marine Science, 2023)
Macroalgae form important coastal ecosystems and are considered to be highly productive, yet individual macrophyte carbon uptake rates are poorly documented and methodologies for in situ assessments of productivity are not well developed. In this study, we employ a 13C enrichment method in benthic chambers to calculate carbon uptake rates and assess δ13C signatures of a large stock of nearshore benthic macroalgae varying in taxa and morphology in Southern California. Our objectives are to 1) identify the variability of carbon uptake and inorganic carbon use among individuals of the same species or morphology, and 2) establish accurate and accessible carbon uptake procedures for coastal benthic primary producers. We found no significant relationship between the observed ranges of environmental factors such as nutrient concentrations, PAR, temperature, conductivity, and productivity rates, suggesting that unique physiological complexions underpin the high variability of carbon uptake and δ13C in studied macrophyte samples. We consider three reasons our experimental carbon uptake rates are 3–4 orders of magnitude lower than existing literature, which reports carbon uptake in the same units despite using different methods: 1) underrepresentation of Pmax, 2) incomplete carbon fractionation corrections, and 3) reduced hydrodynamics within the benthic chambers.